On nash equilibria in speculative attack models - Ivan Pastine (University College Dublin, UCD School of Economics, 2016)
Since a fixed exchange rate regime is a fixed price system, there is no theoretical reason to presume that the foreign exchange market clears, particularly during a speculative attack. This paper shows that equilibria where we allow for the possibility of such corner solutions are a superset of the previously examined "market-clearing" equilibria. The timing of the balance-of-payments crisis is no longer predictable in the same sense - multiple equilibria exist even in the very simplest speculative attack model.
Keywords: F31; E58; 330